Crime organizado: Uma concepç\~ao introdutória - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper expounds an introductory conception of organized crime, resorting to a few elements of conceptual, economic, institutional and strategic analysis. It seeks to build a preliminary overview of a social phenomenon, leaving out the perspectives of law and legislation. Discussing meanings of the phrase organized crime, it presents the two senses put forth by Schelling. It calls attention to notions of firm put forward by Papandreou, Williamson, and Cyert and March, which are richer than the usual notions, as well as to Benjamin Ward's model of the Illyrian firm. Equipped with these notions, a researcher can make useful comparisons of criminal organizations with firms. It deals also with classification of criminal organizations, advantages in organizing, factors of violence, and mafias.
Keywords: K42; 330; criminal organization; Illyrian firm; factors of violence